Overcitation and overrepresentation of review papers in the most cited papers. Issue 4 (November 2018) - Miranda, Ruben; Garcia-Carpintero, Esther
Highlights: Reviews are cited, on average, 3 times more than original research articles. There are large differences in overcitation of reviews depending on research area. Reviews are also overrepresented in the most cited publications. Publication of reviews can greatly impact the citation output of a researcher. A 20% reviews can increase 40%–80% the average citations of an individual. Abstract: Review papers tend to be cited more frequently than regular research articles. This fact, together with the continuous increase of the share of reviews in scientific literature, can have important consequences for the measurement of individuals' research output, usually based on citation analysis. However, studies evaluating the differences in citations of review papers compared to original research articles are almost non-existing in the literature. This paper presents a thorough analysis of the overcitation and overrepresentation of review papers in the most cited papers of the 35 largest subject categories in Science Citation Index-Expanded. Results indicate the average citations received by reviews depends largely on the research area considered, varying from 1.34 to 6.74 times the citations received by original research articles (average value is 2.95). Correlated with this overcitation, there is an important overrepresentation of reviews in the most cited papers, this overrepresentation being greater when the most highly cited papers are considered, i.e. 0.05% and 0.1% most cited papers, where the share of reviews have increased from 16 to 18% in 1990 to around 40% in 2010. Interestingly, the overcitation and overrepresentation in the most cited papers is more important in the areas with the lowest shares of reviews in total publications.